Human acclimatization and adaption to stresses - Rushall, B. S. (1994)
To better understand the mechanisms and dispositions of humans when reacting to altitude author explains some general principles of human acclimatization and adaptation. He mentiones four main features that modify acclimatization responses and underlines important things especially for athletes.